Frugal innovation and the new product development process : insights from Indonesia /: insights from Indonesia. (2019) - Cadeddu, Stephanie B. M; Donovan, Jerome D; Topple, Cheree; de Waal, Gerrit A; Masli, Eryadi K
No abstract available